2000
DOI: 10.1002/(sici)1097-4601(2000)32:3<184::aid-kin9>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of complex formation of 2-methoxyphenol with ferric ion and hexacyanoferric ion

Abstract: Complexes containing one molecule of organic ligand have been formed in the reaction of 2 methoxyphenol with ferric ion or hexacyanoferric ion. Kinetic investigations showed that the reaction order with respect to ferric ion or hexacyanoferric ion is close to one. The reaction order with respect to 2-methoxyphenol is 0.8 in the reaction with ferric ion and close to 0 in the reaction with hexacyanoferric ion. The reaction mechanism, based on kinetic investigations, involves the decomposition of the initial comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The studies on kinetics and elucidation of mechanism of uncatalyzed and catalyzed ligand substitution reactions of transition metal complexes in aqueous medium have received considerable attention by many chemists and environmentalists over the last century for their immediate application in synthetic 1–4 and analytical chemistry 5–7. Ligand substitution reactions of low‐spin iron(II) complexes have been the subject of several kinetic and spectroscopic investigations, and the majority of them are centered around kinetic and mechanistic studies of substitution in hexacyanoferrate(II) 8–12 by nitrogen heterocyclic ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The studies on kinetics and elucidation of mechanism of uncatalyzed and catalyzed ligand substitution reactions of transition metal complexes in aqueous medium have received considerable attention by many chemists and environmentalists over the last century for their immediate application in synthetic 1–4 and analytical chemistry 5–7. Ligand substitution reactions of low‐spin iron(II) complexes have been the subject of several kinetic and spectroscopic investigations, and the majority of them are centered around kinetic and mechanistic studies of substitution in hexacyanoferrate(II) 8–12 by nitrogen heterocyclic ligands.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a considerable advancement in the past few years concerning the kinetics and mechanism of ligand substitution reactions of catalysed and uncatalysed transition metal complexes in aqueous medium. 115 Previous studies revealed that the transition metals, exhibiting complexes like [M(CN) 5 L] n − (where M(II/III) = Fe, Ru and L = H 2 O, CN − , imides) show wide applications towards physiological as well as industrial approaches. 16–23 Numerous transition metal ions, alone or as binary mixtures, such as osmium(III) oxide, palladium(II) chloride, ruthenium(III) chloride, platinum(IV) chloride and iridium(III) chloride, have been used extensively in redox reactions as a homogeneous catalysts, and some systems among these have been proved quite suitable for the purpose of kinetic analysis.…”
Section: Introductionmentioning
confidence: 99%